2013
DOI: 10.1080/11250003.2013.853326
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance and gill histopathological alterations inLiza aurataRisso, 1810 (Actinopterygii: Mugilidae) fry

Abstract: Gill histopathological alterations in Golden Grey Mullet, Liza aurata, fry in acute salinity exposure were studied by light and scanning electron microscopy (SEM). The Golden Grey Mullet fry was obtained from the south of the Caspian Sea and acclimated to brackish water (12 ppt). Fry (adapted in 12 ppt salinity) were transferred directly to salinities of 40, 45, 50, 55, 60, 65 and 70 ppt. Mortality occurs more rapidly over a narrow range of salinity from 45 to 60 ppt. Mortality was 100% in salinity higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Therefore, histopathological changes in gills and other organs (such as the liver and kidney) can be used as an indicator in evaluating the effects of various types of stress in fish (especially salinity). Chloride cells in the epithelium of the gills are the most important cells for ion exchange, and the structure of these cells changes with changes in the salinity of the environment [13]. Since fish are in direct contact with the surrounding aquatic environment, changes in the physicochemical parameters of water such as salinity affect them.…”
Section: Stress Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, histopathological changes in gills and other organs (such as the liver and kidney) can be used as an indicator in evaluating the effects of various types of stress in fish (especially salinity). Chloride cells in the epithelium of the gills are the most important cells for ion exchange, and the structure of these cells changes with changes in the salinity of the environment [13]. Since fish are in direct contact with the surrounding aquatic environment, changes in the physicochemical parameters of water such as salinity affect them.…”
Section: Stress Parametersmentioning
confidence: 99%
“…Therefore, histopathological changes in gills can be used as a marker to evaluate the effects of salinity on fish. Chloride cells in the epithelium of the gills are the most ion exchange cells, and environmental salinity fluctuations change the structure of these cells [13]. Since the fish are in direct contact with the surrounding aquatic environment, changes in the physicochemical parameters of the water such as salinity affect the physiological response of the fish [14].…”
Section: Introductionmentioning
confidence: 99%
“…Shahriari Moghadam et al (2013) investigated the primary target organ for acute salinity effects in Liza Aurata and reported that it affects the type of chloride cells and gill structure.…”
Section: Histological Changes In Eutroplus Suratensis At Varying Sali...mentioning
confidence: 99%